Magnetic Resonance Elastography of Liver: Current Status and Future Directions - Chatterjee, Argha; Miller, Frank H.; Pang, Emily (Journal of Gastrointestinal and Abdominal Radiology, 2024)
Chronic liver disease (CLD) has been recently recognized as a major public health priority. Assessment of presence and degree of liver fibrosis is critical to the management of CLD and traditionally required a liver biopsy. However, biopsy has many limitations including the risk of complications and sampling error. Magnetic resonance elastography (MRE) has emerged as a noninvasive and highly accurate technique for evaluating liver fibrosis. In this comprehensive review, we will delve into the current uses and guidelines for the usage of MRE in CLD, highlighting its advantages and limitations.
Keywords: liver fibrosis; metabolic dysfunction-associated steatohepatitis; quantitative imaging